The Mesozoic Along‐Strike Tectonometamorphic Segmentation of Longmen Shan (Eastern Tibetan Plateau). Issue 12 (18th December 2018) - Airaghi, L.; de Sigoyer, J.; Guillot, S.; Robert, A.; Warren, C. J.; Deldicque, D.
Abstract: The Longmen Shan belt (eastern border of the Tibetan plateau) constitutes a tectonically active region as demonstrated by the occurrence of the unexpected 2008 M w 7.9 Wenchuan and 2013 M w 6.6 Lushan earthquakes in the central and southern parts of the belt, respectively. These events revealed the necessity of a better understanding of the long‐term geological evolution of the belt and its effect on the present dynamics and crustal structure. New structural and thermobarometric data offer a comprehensive data set of the paleotemperatures across the belt and P ‐ T estimates for low‐grade metamorphic domains. In the central Longmen Shan, two metamorphic jumps of 150–200 °C, 5–6 kbar and ~50 °C, 3–5 kbar acquired during the Early Mesozoic are observed across the Wenchuan and Beichuan faults, respectively, attesting to their thrusting movement and unrevealing a major decollement between the allochtonous Songpan‐Garze metasedimentary cover (at T  > 500 °C) and the autochtonous units and the basement ( T  < 400 °C). In the southern Longmen Shan, the only greenschist facies metamorphism is observed both in the basement (360 ± 30 °C, 6 ± 2 kbar) and in the metasedimentary cover (350 ± 30 °C, 3 ± 1 kbar). Peak conditions were reached at ca. 80–60 Ma in the basement and ca. 55–33 Ma in the cover, ca. 50 Ma after the greenschist facies metamorphic overprint observed in the central Longmen Shan (ca. 150–120 Ma). This along‐strike metamorphic segmentation coincides well with the present fault segmentation and reveals that the central and southern Longmen Shan experienced different tectonometamorphic histories since the Mesozoic. Key Points: Metamorphic jumps of ~150 °C, 5 kbar and ~50 °C, 3 kbar are observed across the Wenchuan and Beichuan faults, respectively P ‐ T ‐ t conditions for the southern Longmen Shan, lower than for central Longmen Shan, do not exceed 395 °C and 6 ± 2 kbar (at 80–33 Ma) Different segments of the Longmen Shan underwent different tectonometamorphic evolution since the Mesozoic